S91 Aspergillus fumigatus sensitisation in patients with chronic obstructive pulmonary disease. (2nd December 2011) - Bafadhel, M; Agbetile, J; Fairs, A; Desai, D; Pancholi, M; Mistry, V; Pavord, I D; Wardlaw, A J; Pashley, C H; Brightling, C E
Abstract : Background: Bacteria and viruses have been implicated in exacerbations of chronic obstructive pulmonary disease (COPD) and bacteria are often isolated in stable state. Whether fungi are also commonly present and associated with clinical and pathological features of disease is uncertain. Objectives: To determine the frequency of filamentous fungal culture and sensitisation to Aspergillus fumigatus in COPD and its relationship to clinical outcomes. Methods: Subjects with COPD were recruited from a single centre into a 1-year observational study. Assessments of lung function, allergen testing, and sputum analysis for inflammation, bacterial and fungal cultures were undertaken in COPD subjects and in smoking healthy controls. Results: Fungi were cultured at baseline in 63/128 subjects of which 47/63 were A fumigatus . A fungus was cultured in 2/11 controls (both were A fumigatus ). The total sputum cell count, sputum neutrophil % and inhaled corticosteroid dosage were significantly increased in COPD patients with a positive fungal culture compared to those without a fungal culture (p<0.05), but the within subject repeatability of fungal culture between stable visits was low (K=−0.04). Sensitisation to A fumigatus was present in 13% of COPD subjects and was associated with worse lung function (FEV1 % predicted 39% vs 51%; p=0.01), but not related to fungal culture. Positive fungal cultures were present in 42/110 exacerbations and were not associated with bacterial culture or severity of exacerbation. Conclusions: A fumigatus sensitisation is related to poor lung function. Positive fungal culture is a common feature of COPD. The clinical significance of this remains uncertain.